Pedagogical Innovation in Islamic Educational Institutions: A Systematic Literature Review of the Shift from Traditional to Modern Learning Paradigms - Hafizul Husni; M. Sirozi; Mardiah Astuti; Muhamad Ikhsanudin; Fiksi Juita; Tajuddin Hamzah (Dirasah International Journal of Islamic Studies, 2026)
This study aims to analyze pedagogical innovation in Islamic educational institutions and examine the paradigm shift from traditional teacher-centered learning toward modern student-centered learning approaches. The research employs a Systematic Literature Review (SLR) method following the PRISMA framework to synthesize relevant literature on learning innovation in Islamic education. Data were collected from the Scopus database, resulting in 120 initial articles, of which 20 articles met the inclusion criteria and were analyzed in depth. The findings indicate that pedagogical innovation in Islamic education is primarily reflected in the integration of digital technologies, the adoption of inquiry-based and problem-based learning approaches, the implementation of experiential and contextual learning, and the use of multimedia and interactive learning tools in Islamic studies. The review also reveals a significant paradigm shift from traditional teacher-centered learning toward more flexible, student-centered, and technology-supported learning environments. However, several challenges remain, including limited technological infrastructure, low digital literacy among educators, and the need to maintain Islamic ethical values within digital learning environments. Furthermore, the study proposes a conceptual model of pedagogical innovation in Islamic education that integrates technological development, learner-centered pedagogy, and value-based Islamic education. This model emphasizes that successful innovation requires a balanced integration of modern educational practices with Islamic moral and spiritual values. The findings contribute to the development of innovative pedagogical frameworks for Islamic educational institutions and provide recommendations for policymakers, educators, and researchers seeking to improve the quality and relevance of Islamic education in the digital era.